2007
DOI: 10.1016/j.cell.2007.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PlGF Inhibits Growth of VEGF(R)-Inhibitor-Resistant Tumors without Affecting Healthy Vessels

Abstract: Novel antiangiogenic strategies with complementary mechanisms are needed to maximize efficacy and minimize resistance to current angiogenesis inhibitors. We explored the therapeutic potential and mechanisms of alphaPlGF, an antibody against placental growth factor (PlGF), a VEGF homolog, which regulates the angiogenic switch in disease, but not in health. alphaPlGF inhibited growth and metastasis of various tumors, including those resistant to VEGF(R) inhibitors (VEGF(R)Is), and enhanced the efficacy of chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
736
3
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 724 publications
(780 citation statements)
references
References 40 publications
31
736
3
6
Order By: Relevance
“…Stimulation of tumour angiogenesis by other pro-angiogenic growth factors in the tumour microenvironment may be one mechanism through which this resistance occurs. Previous work has shown that inhibition of FGF2 or PLGF can overcome acquired resistance to VEGFR2 inhibition in mouse tumour models (Casanovas et al, 2005;Fischer et al, 2007). However, to the best of our knowledge, the direct ability of growth factors to stimulate angiogenesis in human endothelial cells when VEGFR2 is inhibited by sunitinib has not been clearly demonstrated.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Stimulation of tumour angiogenesis by other pro-angiogenic growth factors in the tumour microenvironment may be one mechanism through which this resistance occurs. Previous work has shown that inhibition of FGF2 or PLGF can overcome acquired resistance to VEGFR2 inhibition in mouse tumour models (Casanovas et al, 2005;Fischer et al, 2007). However, to the best of our knowledge, the direct ability of growth factors to stimulate angiogenesis in human endothelial cells when VEGFR2 is inhibited by sunitinib has not been clearly demonstrated.…”
Section: Discussionmentioning
confidence: 87%
“…In support of this latter concept, FGF2 is upregulated in a mouse tumour model of acquired resistance to DC101 (a VEGFR2 inhibitory antibody) and inhibition of FGF2 in combination with DC101 led to improved anti-tumour responses (Casanovas et al, 2005). Moreover, inhibition of PLGF or PDGF has been reported to enhance the anti-tumour efficacy of VEGF pathway inhibitors in some murine tumour models (Bergers et al, 2003;Fischer et al, 2007;Crawford et al, 2009). Another recent study demonstrated that IL-8 is upregulated in sunitinib-resistant tumour xenografts and that inhibition of IL-8 can re-sensitize these resistant tumours to sunitinib (Huang et al, 2010b).…”
Section: Introductionmentioning
confidence: 94%
“…Anti-Bv8 antibody treatment resulted in a significant decrease of tumor growth and a reduction in CD11b + Gr1 + cell mobilization from the bone marrow. Placenta growth factor (PlGF), a VEGF-family member binding only to VEGFR-1, has been reported to contribute to the recruitment of myeloid cells into the tumor microenvironment (Fischer et al, 2007). Blocking PlGF results in the inhibition of monocyte/macrophage recruitment to tumor sites, reduced tumor angiogenesis and tumor growth, in particular in combination with anti-VEGF therapy (Fischer et al, 2007).…”
Section: Tumor Necrosis Factor (Tnf)mentioning
confidence: 99%
“…Placenta growth factor (PlGF), a VEGF-family member binding only to VEGFR-1, has been reported to contribute to the recruitment of myeloid cells into the tumor microenvironment (Fischer et al, 2007). Blocking PlGF results in the inhibition of monocyte/macrophage recruitment to tumor sites, reduced tumor angiogenesis and tumor growth, in particular in combination with anti-VEGF therapy (Fischer et al, 2007). The role of PlGF in tumor angiogenesis, and its value as potential therapeutic target, however, is matter of controversy (Bais et al, 2010;Van de Veire et al, 2010).…”
Section: Tumor Necrosis Factor (Tnf)mentioning
confidence: 99%
“…Various studies have reported that TAMs counteract the efficacy of anti-angiogenic agents. For example, TAM depletion with clodronate liposomes synergizes with sorafinib in human hepatocellular carcinoma xenograft models [141] and with the anti-VEGFR2 antibody, DC101, in subcutaneous colon tumors [142] to reduce tumor growth. Synergy also occurs when combining a CSF1R inhibitor with DC101 in another transplantable model [143].…”
Section: Immune Cell Function Following Vascular-targeting Agentsmentioning
confidence: 99%